A Value Chain Approach to Forest Landscape Restoration: Insights from Vietnam’s Production-Driven Forest Restoration (Forest and Society, 2022)
According to FAO figures, over 129 million hectares of forests have been lost globally since the 1990s, mainly in the tropical Global South, where agriculture acts as the main driver of forest conversion. International commitments, such as the Bonn Challenge, aim to reverse this trend through the application of forest landscape restoration (FLR) as an integrated and inclusive restoration approach. Beyond the discourse level, however, FLR implementation lags behind expectations due to insufficient funding and a disconnection with local implementation. We argue that, instead of relying on public resources for conservation-driven restoration, increased private sector engagement may point the way out of the funding impasse. However, this requires a shift towards production-driven FLR, which includes the livelihood needs of communities and smallholders as agents of landscape transition. For achieving the dual purpose of connecting landscapes with markets and promoting sustainable landscape restoration, we ascribe value chains and their economic, social and ecological configurations a key role in production-driven FLR. Drawing on Vietnam’s forest restoration pathway as an illustrative case, we examine how production-driven forest restoration, smallholder engagement and value chain upgrading can stimulate positive landscape transitions. We conclude that, depending on their configuration, value chains can have negative or positive social and ecological impacts at the landscape level. Furthermore, regulated, progressive and high-value commodity chains may perform better in the areas of integrated FLR objectives landscape integrity, ecological functionality and human well-being.
Keywords: forest landscape restoration; production-driven; vicious and benign value chains; tree plantations; acacia; smallholder inclusion; certification; landscape mosaic; Vietnam